Polyphenols : properties, recovery, and applications - Galanakis, Charis M. (Woodhead Publishing, 2018)
Polyphenols: Properties, Recovery, and Applications covers polyphenol properties, health effects and new trends in recovery procedures and applications. Beginning with coverage of the metabolism and health effects of polyphenols, the book then addresses recovery, analysis, processing issues and industrial applications. The book not only connects the properties and health effects of polyphenols with recovery, processing and encapsulation issues, but also explores industrial applications that are affected by these aspects, including both current applications and those under development.